Electrodermal Screening of Asthmatics with AcuGraph 4 - Kuntal Ghosh; Alex Hankey; Thaiyar M. Srinivasan (Medical Association of Pharmacopuncture Institute, 2017)
Traditional Chinese Medicine holds that acupuncture meridian activity is correlated with quality of function of specific organs. This study sets out to determine acupuncture meridian characteristics of subjects with moderate asthma distinguishing them from healthy subjects. Fifty asthma patients (age 35.36 ± 8.68 years) and fifty similarly aged (34.11 ± 7.29 years) healthy volunteers were enrolled in the study. Electrodermal conductances at Jing Well points were measured with Acugraph 4 and also Peak Expiratory Flow Rate (PEFR) for the asthma group. All mean meridian conductances were lower for the asthma group, significance differences were in Lung and right Bladder meridians. In contrast, all but two of the standard deviations of group meridian conductances for the Asthma group were higher than those for the Healthy group. Difference in mean PEFR values between Asthma and Healthy groups was significant. These suggest that group measures of electrical conductance at Jing Well points can distinguish asthma from healthy individuals. The study provides support for the usefulness of meridian energy measurements to assess organ related dysfunction and for the idea that pathology groups exhibit higher standard deviations i.e. lower quality of regulation.